Simulation Tools to Analyze the Impact of Industries Installation - Adamatti, Diana Francisca; Nunes, Gerson Leiria; Thomassi, Camila Dasso; Jugueiro, Marcio; Gularte, Alexander (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2015)
This paper presents a simulator that analyzes the impacts of the pollutants emission of a new industry insertion on a specific region (in our studies, at Rio Grande City – Brazil). This simulation calculates the atmosphere pollutants concentration and the user can chose between three pollutants dispersion models to simulate: a hypothetic model, ISC model or CALPUFF model, all of them were integrated to GIS.